2022
DOI: 10.52054/fvvo.14.3.033
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering evidence-based management of endometriosis

Abstract: Background: Without an adequate animal model permitting experiments the pathophysiology of endometriosis remains unclear and without a non-invasive diagnosis, information is limited to symptomatic women. Lesions are macroscopically and biochemically variable. Hormonal medical therapy cannot be blinded since recognised by the patient and the evidence of extensive surgery is limited because of the combination of low numbers of interventions of variable difficulty with variable surgical skills. Experience is spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 87 publications
0
30
0
1
Order By: Relevance
“…Bayesian statistics is thought to provide a probabilistic framework that reduces the instability of the data. It can also omit limitations of traditional statistics when comparing parametric and non-parametric data, especially in endometriosis in which symptoms, the clinical experience of the doctor, and the patient’s needs are the most important factors in the diagnosis and treatment [ 32 ]. Looking for a non-invasive test for endometriosis, one should nowadays keep these new statistical tools in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian statistics is thought to provide a probabilistic framework that reduces the instability of the data. It can also omit limitations of traditional statistics when comparing parametric and non-parametric data, especially in endometriosis in which symptoms, the clinical experience of the doctor, and the patient’s needs are the most important factors in the diagnosis and treatment [ 32 ]. Looking for a non-invasive test for endometriosis, one should nowadays keep these new statistical tools in mind.…”
Section: Discussionmentioning
confidence: 99%
“…This diversity underscores the need for a nuanced approach rather than a blanket recommendation for fertility preservation (FP) in all endometriosis patients. 49 Stratification criteria should be explored to identify those most likely to benefit from FP interventions. Secondly, the distinction between the disease itself and the potential adverse effects of treatment modalities on ovarian reserve deserves attention.…”
Section: Discussionmentioning
confidence: 99%
“…It's crucial to recognise that the severity of endometriosis, as determined by staging, does not always correlate directly with the extent of symptoms experienced by the patient. 49 Similarly, this lack of direct correlation extends to its impact on fertility, as cases of stage four endometriosis with rectal involvement may not necessarily have a more profound effect on fertility compared to instances involving ovarian endometriomas, highlighting the intricate and multifaceted nature of the disease's influence on reproductive health. 50,51 Early evidence suggested that laparoscopic excision of any visible endometriotic lesions in early stages of the disease, seem to improve the fecundity of these women, however that does not justify aggressive surgical treatments.…”
Section: The Impact Of Endometriosis On Fertility Performancementioning
confidence: 99%
“…Lesions appear in different forms as they progress from new clear/white, to red, then black lesions 6,7 and finally a white scar reflecting a loss of endometrial glands and stroma and increased collagen deposition 8 . However, macroscopically similar lesions have different behaviors and can cause different symptoms 4 . Lesion morphology is also heterogenous.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis research, diagnosis, treatment and management is complicated by the heterogeneity of the disease 4 . The number or location of lesions does not correlate with symptoms 5 and for some patients, the disease is discovered when they undergo explorative laparoscopy for unexplained infertility.…”
Section: Introductionmentioning
confidence: 99%